Abai vocal cycle of E.Rakhmadiev: interpretation of the genre - Егинбаева, Тойжан; Момбек, Алия (Pedagogy and Psychology, 2020)
The article examines the musical creativity of E.Rakhmadiev, a classic of the Kazakh composing school, the author of vocal-symphonic, opera, chamber-instrumental, song-choral works that are included in the national musical treasury. The author of article presents an analysis of the vocal cycle of seven romances dedicated to the legacy of Abai. In the cultural life of the Kazakh people, the personality of Abai Kunanbayev, his poetic and musical creativity occupy a special place. Each of his poem “sings”, and it is not surprising that many composers, when creating their songs and romances, turn to the poetic heritage of Abai. In each of the romances the organic unanimity of the composers and the poet is manifested, each of the songs is self-sufficient and has its own musical and poetic content, all romances differ from each other both genre and stylistically.